The Potential Threat Of Iran's Nuclear Conflict To Nuclear Proliferation In Southeast Asia - Djakaria, As'ad Syamsul Arif (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
This study examines the potential impact of Iran's nuclear program on the perceptions of security in Southeast Asia, highlighting how Iran's resilience under international pressure could influence ASEAN nations. Using the diffusion of norms theory, the paper identifies Iran's actions as a precedent that may inspire similar pursuits in the region, threatening regional stability. It further explores Indonesia's strategic role in addressing this challenge through diplomatic initiatives, proactive leadership in ASEAN frameworks, and the development of peaceful nuclear technology. Strengthened collaboration with international bodies such as the IAEA and robust regional policies are essential to ensure nuclear development remains focused on peaceful purposes. Indonesia’s leadership in advocating non-proliferation, fostering regional cooperation, and mediating conflicts is critical to maintaining Southeast Asia as a nuclear-weapon-free zone. The findings underline the need for comprehensive strategies to mitigate proliferation risks while enhancing regional security and stability.